Trade Openness and Inclusive Economic Growth: Poverty Reduction through the Growth – Unemployment Linkage - Warrad, Taleb Moh'd; Muhtaseb, Buthaina M.A. (International Journal of Economics and Financial Issues, 2017)
This paper investigates the relationship between trade and poverty reduction through the channels of economic growth and employment. Two econometric models are utilized to analyze these interconnected linkages for Jordan during the 1980–2014 period. The first model, which is based on a theoretical framework developed for this purpose, estimates the impact of trade, among other factors, on economic growth by applying heteroskedasticity-corrected OLS estimation method. We further, extended the analysis by employing the second model on the basis of OKun's Law to examine the effect of economic growth on unemployment. The findings of the study suggest that external factors are the major contributors to growth, especially workers' remittances, followed by external trade and then FDI inflows. But the achieved growth has not been sufficiently reflected on unemployment reduction and poverty alleviation, due to the inflated government, fast population growth combined with the flux of foreign labor and refugees. Keywords: Trade Openness, OKun's Law, Poverty, FDI, Inclusive Economic Growth. JEL Classifications: F1, I3, O4